PETANI PENGGARAP KEBUN KELAPA SAWIT - Faril Antama Fani; Erfahmi Erfahmi (Universitas Negeri Padang, 2020)
The creation of this final work aims to visualize oil palm farmers in contemporary realist paintings. Showing the activities of oil palm growers. The method and process of making works carried out in the creation of art works begin several steps: (1) Preparation, (2) Elaboration, (3) Synthesis, (4) Realization of Concepts, (5) Completion. The results of the visualization of oil palm growers reveal the activities of oil palm farmers in their work. Which is manifested in 10 works with the titles: (1) enduring, (2) struggles, (3) discarding, (4) pioneering, (5) surviving, (6) hoping, (7) weighing, (8) launching, (9) ) weigh # 2, (10) cultivate.